2020
DOI: 10.1002/er.5893
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of cerium‐doped Co 3 O 4 nanoflakes as electrode for supercapacitor application

Abstract: Summary In this work, cerium was doped in various concentrations ranging from 1.0 to 7.0 at. % by means of a facile hydrothermal synthesis route with an intention to improve the capacitive properties of Co3O4. X‐ray powder diffraction (XRD), scanning electron microscopy coupled with energy dispersive X‐ray spectroscopy (EDX) and HRTEM were employed to study the structural characteristics, morphology, elemental constitution and d‐spacing of the synthesized material. The capacitive characteristics were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…The four symmetrical charge/discharge platforms correspond to the four pairs of redox peaks in CV curves, and the nonlinear characteristics of the GCD curves expose the typical faradic characteristics of OV‐MoO 3 and OV‐MoO 3 /Ce. [ 32 ] Figure 6d shows the specific capacitance of OV‐MoO 3 and OV‐MoO 3 /Ce at 5–20 A g –1 . The specific capacitance of OV‐MoO 3 /Ce = 30/1 is 1446.3 F g –1 at 5 A g –1 and 979 F g –1 at 20 A g –1 , respectively, greater than OV‐MoO 3 (1146.2 F g –1 and 515 F g –1 ), OV‐MoO 3 /Ce = 40/1 (1366.9 F g –1 and 817.5 F g –1 ), and OV‐MoO 3 /Ce = 20/1 (876.2 F g –1 and 470.0 F g –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The four symmetrical charge/discharge platforms correspond to the four pairs of redox peaks in CV curves, and the nonlinear characteristics of the GCD curves expose the typical faradic characteristics of OV‐MoO 3 and OV‐MoO 3 /Ce. [ 32 ] Figure 6d shows the specific capacitance of OV‐MoO 3 and OV‐MoO 3 /Ce at 5–20 A g –1 . The specific capacitance of OV‐MoO 3 /Ce = 30/1 is 1446.3 F g –1 at 5 A g –1 and 979 F g –1 at 20 A g –1 , respectively, greater than OV‐MoO 3 (1146.2 F g –1 and 515 F g –1 ), OV‐MoO 3 /Ce = 40/1 (1366.9 F g –1 and 817.5 F g –1 ), and OV‐MoO 3 /Ce = 20/1 (876.2 F g –1 and 470.0 F g –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Metal-ion doping is a suitable way to improve the electrochemical performance of active materials in supercapacitors by enhancing the electrical conductivity and increasing active sites. [21][22][23] Li et al synthesized Mn-doped Co 3 O 4 nanoneedles to enhance the electrochemical activity and conductivity of Co 3 O 4 by increasing active sites and facilitating fast charge transportation. 21 Aadil developed a mesoporous material of Ag-doped Co 3 O 4 nanosheets to increase the electrochemical properties through tuning the bandgap and improving the SSA by doping Ag into Co 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Ali et al reported Ce doped Co 3 O 4 nanoakes to improve the electrical conductivity and specic capacitance by shortening the ion transportation path and increasing the active surface area. 23 In this work, we developed a facile strategy to synthesize hierarchical seedling-like porous nanowires of spinel Co 3 O 4 partially substituted by Sn on GF through a hydrothermal method and subsequent thermal annealing process. The unique CSO@GF structure showed improved electrochemical properties due to its signicantly enhanced electrical conductivity, which was investigated by density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The Ce–Co 3 O 4 catalyst was synthesized via a facile hydrothermal method, as depicted in Figure a. [ 18,19 ] Detailed synthesis information can be found in the Experimental Section (Supporting Information). For comparison, the pure Co 3 O 4 was prepared using the same procedure without the addition of CeCl 3 ·6H 2 O. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques were employed to investigate the morphologies of both Ce–Co 3 O 4 and Co 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%